ANALISIS DINAMIKA NILAI TUKAR PETANI DI PROVINSI NUSA TENGGARA TIMUR: IMPLIKASI TERHADAP KESEJAHTERAAN PETANI DAN KEBIJAKAN PERTANIAN - Maria Gratia Fernandez (Badan Pusat Statistik Provinsi NTT, 2025)
This study aims to analyze the dynamics of Farmer Terms of Trade (FTT) in East Nusa Tenggara Province and its implications for farmer welfare and agricultural policy formulation. East Nusa Tenggara Province, despite being an agricultural-based region contributing 28.83% to regional GDP, faces persistent challenges in farmer welfare as indicated by fluctuating FTT values. The monthly FTT data from January to August 2025 shows volatility with values ranging from 99.08 to 101.93, frequently falling below the break-even point of 100, indicating that farmers experience deficit conditions where production costs exceed income. This research provides a comprehensive analysis of subsectoral FTT dynamics in East Nusa Tenggara, identifying specific variations across five agricultural subsectors (food crops, horticulture, plantation crops, livestock, and fisheries) and proposing targeted policy interventions based on empirical evidence from recent data spanning JanuaryAugust 2025. This study employs descriptive statistical analysis using secondary data from the Central Bureau of Statistics of East Nusa Tenggara Province. The analysis includes monthly FTT calculations, subsectoral decomposition, price index received (IT) and price index paid (IB) by farmers, and comparative analysis across different agricultural subsectors during the period of January-August 2025. The research reveals that: (1) FTT in East Nusa Tenggara experienced significant fluctuations with an overall declining trend from January (101.60) to July 2025 (99.08) before recovering in August (101.93); (2) Livestock subsector demonstrated the highest FTT at 107.89, while fisheries recorded the lowest at 93.44; (3) The volatility in FTT is primarily driven by faster increases in the price index paid by farmers compared to the price index received, particularly affecting production costs; (4) Four subsectors (food crops, horticulture, plantation crops, and fisheries) consistently recorded FTT values below 100, indicating welfare challenges; (5) Rural deflation of -0.35% in June 2025 significantly impacted farmer purchasing power.